EVOLUTION OF THE MAIN INDICATORS OF PUBLIC DEBT SUSTAINABILITY IN THE PERIOD 2014-2018 IN ROMANIA - Luiza Madalina APOSTOL (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
Romania's public debt is below the value registered by most of the EU member states, but its accelerated evolution and the pro-cyclical nature of the fiscal policy require a careful evaluation. The sustainability of the public finances must be a major challenge for the public policies. In order to maintain a sustainable level of the public debt, it is necessary to achieve the medium-term budgetary objective, to ensure a downward trend of the public debt share in the gross domestic product, by strictly observing the rules of budgetary policy. This paper shows an analysis of the public debt sustainability in Romania, for the period 2014 - 2018.